Representasi Komunikasi Kelompok Keluarga dalam Serial Drama Korea: Studi Analisis pada “Reply 1988” - Herlambang Yudha Prasetya; Dani Fadillah (SENTRI: Jurnal Riset Ilmiah, 2026)
Television dramas, particularly Korean dramas, have emerged as influential forms of popular media that disseminate and reinforce discourses surrounding family values in the era of globalization. Despite the growing popularity of Korean dramas, limited attention has been given to how family communication is represented as a medium for transmitting sociocultural values. This study aims to analyze the representation of family communication in the Korean drama Reply 1988, focusing on how sociocultural values are constructed through verbal and non-verbal interactions among family members. Employing a qualitative approach, this study adopts Norman Fairclough’s three-dimensional Critical Discourse Analysis (CDA) framework, which examines text, discursive practice, and social practice, and applies data and theoretical triangulation to enhance the credibility and validity of the findings. The results reveal that family communication in Reply 1988 reflects core Korean cultural values, including filial piety (hyo), intergenerational solidarity, and traditional gender roles. These values are conveyed primarily through cultural symbols and non-verbal expressions, such as body language, gestures, facial expressions, and strategic silence. The communication patterns portrayed in the series extend beyond functional interactions, emphasizing emotional and symbolic dimensions that characterize a high-context communication culture. This study contributes to the literature on family communication and popular culture by demonstrating how television dramas function as media for constructing and reproducing idealized domestic values within contemporary society.